2001
DOI: 10.2337/diacare.24.5.850
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Glucose Tolerance in Transfusion-Dependent β-Thalassemic Patients

Abstract: OBJECTIVE -To study the prevalence of and risk factors for abnormal glucose tolerance in transfusion-dependent ␤-thalassemic patients.RESEARCH DESIGN AND METHODS -A total of 89 transfusion-dependent ␤-thalassemic patients were interviewed. Diabetes was previously diagnosed in 14 of them. In the remaining 75 patients, 68 participated in an oral glucose tolerance test. Potential risk factors were identified using the independent t test, 2 test, and Fisher's exact test. Logistic regression analysis was used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 28 publications
4
74
2
3
Order By: Relevance
“…50% of twenty patients studied by Suadek et al [43] had abnormal glucose tolerance. Sixteen of eighty two patients interviewed by Chern et al had diabetes and risk was increased by co-infection with hepatitis C [44]. Gamberini et al [44] followed up 273 thalassaemic patients over a period of thirty years and have shown that 42 patients developed insulin dependent diabetes mellitus.…”
Section: Glucose Intolerance and Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…50% of twenty patients studied by Suadek et al [43] had abnormal glucose tolerance. Sixteen of eighty two patients interviewed by Chern et al had diabetes and risk was increased by co-infection with hepatitis C [44]. Gamberini et al [44] followed up 273 thalassaemic patients over a period of thirty years and have shown that 42 patients developed insulin dependent diabetes mellitus.…”
Section: Glucose Intolerance and Diabetes Mellitusmentioning
confidence: 99%
“…Sixteen of eighty two patients interviewed by Chern et al had diabetes and risk was increased by co-infection with hepatitis C [44]. Gamberini et al [44] followed up 273 thalassaemic patients over a period of thirty years and have shown that 42 patients developed insulin dependent diabetes mellitus. They demonstrated that prevalence progressively increased with time.…”
Section: Glucose Intolerance and Diabetes Mellitusmentioning
confidence: 99%
“…This is mostly attributed to changes in lifestyle and increase in obesity (Matthews and Matthews 2011). Interestingly, several reports indicate increased risk of diabetes after organ transplant (Kasiske et al 2003;Carey et al 2012) and blood transfusion (Chern et al 2001). New-onset diabetes after organ transplant (NODT), such as kidney transplant, is frequently ob-served in recipients (Kasiske et al 2003;Carey et al 2012).…”
Section: Prion-like Transmission Of Protein Aggregates In "Real Life"mentioning
confidence: 99%
“…Moreover, a recent report indicates that diseased hearts from obese, prediabetic individuals exhibit oligomeric IAPP, suggesting that the process of IAPP accumulation may begin decades before the onset of overt T2D (Despa et al 2012). Increased risk of developing impairment in glucose metabolism and diabetes has also been noted in individuals who have received chronic blood transfusion (Chern et al 2001;Shamshirsaz et al 2003). Iron-overloadmediated toxicity in the endocrine system is believed to be the underlying cause.…”
Section: Prion-like Transmission Of Protein Aggregates In "Real Life"mentioning
confidence: 99%
“…The first mechanism involves decrease in insulin production either by direct impairment of insulin excretory function by chronic iron overload or immune system activation against pancreatic b-cells in b-thalassaemia patients. 16,17 The second mechanism involves decreased insulin sensitivity with reduced hepatic release of insulin. 8,18 Thyroid dysfunction is another frequently occurring endocrine complication.…”
Section: Introductionmentioning
confidence: 99%